Application of a modified method for stem cell isolation from lipoaspirates in a basic lab (Faculty of Medicine Universitas Indonesia, 2009)
Aim Lipoaspirate, a wasted by product from liposuction procedure recently has been shown to contain abundant mesenchymal stem cells (MSCs). MSCs have been studied in many research areas to regenerate many cell lineages including, myogenic, cardiomyogenic, and angiogenic lineages. The large quantity of MSCs in lipoaspirate, makes it an attractive source for stem cells used in research and clinical applications. A simplified method which is suitable to be performed in a basic laboratory will facilitate development of stem cell research in developing countries. Therefore the outcomes from this study are expected to encourage the progress of stem cell research in Indonesia. Methods Lipoaspirate was digested using collagenase type I, followed by a basic filtration method. Purification of MSCs was done by cell culture for 2-3 days followed by supernatant removal. To confirm the homogenous population of MSCs, an analysis using flowcytometry was performed based on the MSCs minimal criteria developed by Mesenchymal and Tissue Stem Cell Committee of the International Society of Cell Therapy. Resuts MSCs were able to be obtained at 16.41 ± 8.22 x 108 cells per 120 ml lipoaspirate. The cultured cells showed fibroblastic morphology which is characteristic for MSCs and were able to be purified from non-MSCs cells. This was confirmed by flowcytometry assay showing expression of CD105 and the absence of HLA-Class II, CD 45, CD 34, CD14, and CD19. Conclusions This study has shown that it was feasible to isolate messenchymal stem cell from human lipoaspirate. The procedure was practicable to be performed within a basic laboratory. (Med J Indones 2009; 18: 91-6)